2021
DOI: 10.1097/dad.0000000000002115
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Melanocytes in Frontal Fibrosing Alopecia: An Immunohistochemical Study With Trichoscopic Correlation

Abstract: Background:Frontal fibrosing alopecia (FFA) is a scarring alopecia that affects the frontotemporal hairline. Clinically, it may develop with cutaneous hypopigmentation of the affected areas, which has been associated with a reduction in the epidermal melanocyte count. In trichoscopy, peripilar white halos can be observed, which have been associated with fibrosis in other scarring alopecias.Objective:To evaluate the trichoscopic, histopathological and immunohistochemical characteristics of the peripilar white h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Dermoscopy has already been reported as a useful tool for the selection of a biopsy site and therefore facilitation of the diagnosis of melanocytic lesions [7,8], cicatricial alopecia [9][10][11][12][13], extramammary Paget's disease [14], melanonychia [15] and penile sclerosing granuloma [16]. Dermoscopy may not only aid selection of the biopsy site but also guide nail abrasion for mycological samples in case of onychomycosis [17].…”
Section: Case Reportmentioning
confidence: 99%
“…Dermoscopy has already been reported as a useful tool for the selection of a biopsy site and therefore facilitation of the diagnosis of melanocytic lesions [7,8], cicatricial alopecia [9][10][11][12][13], extramammary Paget's disease [14], melanonychia [15] and penile sclerosing granuloma [16]. Dermoscopy may not only aid selection of the biopsy site but also guide nail abrasion for mycological samples in case of onychomycosis [17].…”
Section: Case Reportmentioning
confidence: 99%
“…It is also unclear how nevus-associated melanocytes could be protected in this process. 8,9 Previously, Pirmez et al 10 reported the pseudo 'fringe sign' in FFA, defined as sparing of the hairline in the course of the disease. The presented cases do not however represent pseudo 'fringe sign', as hairs were preserved only within and around DNs.…”
mentioning
confidence: 99%